Cotton, tomato, corn, and onion production with subsurface drip irrigation: A review - Lamm, Freddie R. (My University, 2016)
The usage of subsurface drip irrigation (SDI) has increased by 89% in the U.S. during the past ten years according to USDA-NASS estimates, and over 93% of the SDI land area is located in just ten states. Combining public entity and private industry perceptions of SDI in these ten states, the major crops were tentatively identified as cotton, processing tomato, field corn, and onion. An extensive literature review of SDI usage for these four crops was performed concentrating on irrigation system comparisons, water and/or nutrient management, and SDI system design criteria. Although many crops potentially can be grown with SDI, the results presented here may be a relatively representative crosssection of the various opportunities and challenges of SDI for general crop production. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Lamm, F. R. (2016). Cotton, tomato, corn, and onion production with subsurface drip irrigation: A review. Transactions of the Asabe, 59(1), 263-278. doi:10.13031/trans.59.11231
Keywords: Crop Production; Irrigation Methods; Microirrigation; Sdi; Trickle Irrigation; Cotton